2017
DOI: 10.1101/226340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption to functional networks in neonates with perinatal brain injury predicts motor skills at 8 months

Abstract: ObjectiveFunctional connectivity magnetic resonance imaging (fcMRI) of neonates with perinatal brain injury could improve prediction of motor impairment before symptoms manifest, and establish how early brain organization relates to subsequent development. Methods: This cohort study is the first to describe and quantitatively assess functional brain networks and their relation to later motor skills in neonates with a diverse range of perinatal brain injuries. Infants (n=65, included in final analyses: n=53) we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…By contrast, this relationship is not present in preterm neonates before term-equivalent age. Our results in full-term neonates are consistent with a number of previous studies that observed high-order networks in this group (Rajasilta et al, 2020;Linke et al, 2018;He et al, 2016He et al, , 2015Doria et al, 2010)…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…By contrast, this relationship is not present in preterm neonates before term-equivalent age. Our results in full-term neonates are consistent with a number of previous studies that observed high-order networks in this group (Rajasilta et al, 2020;Linke et al, 2018;He et al, 2016He et al, , 2015Doria et al, 2010)…”
Section: Discussionsupporting
confidence: 93%
“…He et al (2015) detected a fronto-parietal network, comprising the frontal gyrus and inferior parietal cortex, and a second one, comprising the anterior cingulate cortex, medial prefrontal cortex, superior/middle frontal gyrus, in preterm neonates. Linke et al (2018) found that both the ECN and DMN were present even in neonates with perinatal brain injuries, both full-term and preterm neonates scanned at TEA. Several factors may contribute to these divergent results.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Evidence for frontal involvement in this task is broadly consistent with recent research suggesting that the frontal cortex plays an important role in infant cognition. [45][46][47] An important limitation of the current study is the inability of fMRI to distinguish whether evidence of statistical learning in the hippocampus originates in the hippocampus or is a reflection of processing in the mPFC, given their connectivity.…”
Section: Reportmentioning
confidence: 98%